Pengaruh Ukuran Perusahaan, KAP, Kualitas Audit, dan Inflasi terhadap Nilai Perusahaan Sektor Transportasi dan Pergudangan di BEI - Michelle, Michelle; Yuniana, Yuniana; Rajagukguk, Ronald Hasudungan; Siahaan, Septony Benyamin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study examines the influence of company size, the size of Public Accounting Firms (KAP), audit quality, and inflation on the value of companies in the transportation and warehousing sectors listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach with an explanatory method to analyze causes and effects, this study took a population of 22 companies in the sector listed on the IDX during the 2020-2023 period. Through the purposive sampling technique, 44 observation samples were obtained which were analyzed by the multivariate regression method. The results show that company size does not have a significant influence on the value of companies in the transportation and warehousing sector. In contrast, the size of the KAP has a significant effect and suggests that companies audited by larger KAP tend to have higher company values, likely due to a better reputation in the eyes of investors. Meanwhile, audit quality and inflation did not have a significant impact on corporate value in this sector, indicating that external factors of inflation and variability in audit quality did not have much impact on the perception of corporate value for investors in this sector. Overall, although company size, KAP size, audit quality, and inflation are not all individually significant, these variables together still show an influence on the value of companies in the transportation and warehousing sectors listed on the IDX. These findings provide insights for management and investors in considering factors relevant to the company's value.